Computer Science
Reduce the following to its simplest form using laws of boolean algebra. At each step clearly state the law used for simplification.
A.B' + A'.B.C' + (A.C') + B.C
Boolean Algebra
19 Likes
Answer
A.B' + A'.B.C' + (A.C') + B.C
= A.B' + A'.B.C' + (A.C')(B+B') + B.C [Complementary Law: B+B'=1]
= A.B' + A'.B.C' + A.B.C' + A.B'.C' + B.C [Distributive Law]
= A.B' + A.B'.C' + A'.B.C' + A.B.C' + B.C [Associative Law]
= A.B' + A'.B.C' + A.B.C' + B.C [Absorbtion Law: A.B' + A.B'.C' = A.B']
= A.B' + B.C + B.C'(A' + A)
= A.B' + B.C + B.C'.1 [Complementary Law: A+A'=1]
= A.B' + B(C + C')
= A.B' + B [Complementary Law: C+C'=1]
= (A + B).(B' + B) [Distributive Law]
= A + B [Complementary Law: B+B'=1]
Answered By
11 Likes
Related Questions
What is the application of boolean algebra in computer science?
Explain the following:
- Canonical sum of product
- Canonical product of sum
Simplify a.b + a'.c + b.c using the laws of boolean algebra. At each step, state clearly the law used for simplification.
State the dual form of the following boolean expression:
X.Y'(X.Y'.Z + X + X'.Z')